The Relevance of the Discourse to ESL Studies: a Review of T. A. Van DIJK's Text and Context: Explorations in the Semantics and Pragmatics of Discourse - Adegbite, Wale (2014)
This paper reviews T. A. Van Dijk's Text and Context: Explorations in the semantics and pragmatics of discourse by summarising the main issues discussed in the work and observing the relevance of the discussion to studies on English as a Second Language (ESL). The review observes that although Van Dijk's work does not provide an adequate theory of English discourse since it only describes the underlying structures of the discourse, and also because it deliberately neglects certain features that are regular to discourse production and interpretation and which are especially of particular interest to discourse studies in an ESL situation, it no doubt provides a good starting point for an adequate theory of English discourse. It also provides a base for more comprehensive studies on the discourse which will have relevance to the pedagogy of English and communication in the language in a natural ESL environment.